Taking Stock, December 2012 : An Update on Vietnam's Recent Economic Developments - Mishra, Deepak; Dinh, Viet Tuan (World Bank, Hanoi, 2017)
This paper includes three parts: external economic environment, part one includes: global environment, regional environment, and risks. Vietnam's recent economic development, part two includes: a relatively stable macroeconomic situation, growth at record low, booming exports despite a slowing economy, sharp turnaround in external accounts, inflation dynamics, monetary policy, fiscal policy, and near-term outlook. Structural reforms and medium-term outlook, part three includes: context, restructuring of state-owned enterprises, banking Sector development, and poverty reduction.